The partner - Grisham, John. (New York : Doubleday, 1997)
Thought killed in a car accident four years earlier, Patrick Lanigan is discovered living in Brazil under the name of Danilo Silva and presumably in possession of millions of dollars missing from his former firm's offshore account
Keywords: Death, Apparent -- Fiction; Larceny -- Fiction; Brazil -- Fiction; Biloxi (Miss.) -- Fiction; Legal stories